Does Ultrasound Feature of Morbidity Adherent Placenta Give Us a Lead to Decide a Uterine Salvage Surgery - Urooj, Uzma; Siraj, Asifa; Tariq, Mahpara; Khan, Sumaira; Akram, Shaheera; Afzal , Shazia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To correlate and confirm the ultrasonography diagnosis of placenta accreta spectrum with surgical findings.Study Design: Cross-sectional study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Aug 2023 to Apr 2024.Methodology:  During pregnancy, ultrasound is a frequently utilised imaging modality that provides a non-invasive way to evaluate the placenta's features as well as its characteristics. The cohort comprised women with placenta previa and a history of at least one prior cesarean section or any other uterine surgery.Results: The mean maternal age was 23.6±5.1years and mean gestational age at birth was reported as 34.3±2.5 weeks. In comparing each sonography index, the presence of bladder interruption (kappa: 0.838, sensitivity: 86%, specificity: 100%) and subplacental hypervascularity (kappa: 0.808, sensitivity: 85.3%, specificity: 95%) demonstrated the highest concordance for diagnosing PAS when evaluated against the gold standard diagnosis. Pateints diagnosed with PAS 1,2,3, on ultrasound were 59(71.9%). PAS 1 were 19(23.1%), PAS 2 were 26(31.7%) and PAS 3 were 14(17.07%).  Upon surgical correlation, out of these 59 patients 48(81.3%) were surgically confirmed to have PAS. Out of these sugically confirmed patients, PAS 1 was in 14(73.6%), PAS 2 in 23(88.4%) and PAS 3 was in 13(92.8%) of patinets. Adverse surgical outcomes occurred in 11.8% of pregnancies, with a 95% confidence interval ranging from 7.9% to 17.2%.Conclusion:  Ultrasound diagnosis plays a crucial role not only in detecting placental invasion but also in facilitating its preliminary classification as it was confirmed during surgery.